LOCAL COMMUNITY ATTITUDE AS A SUCCESS FACTOR IN A TOURISM PROJECT - Shomurodova Ozoda Uygun qizi (Journal of new century innovations, 2023)
Abstract: Tourism development planning and management are not possible if local population attitudes towards tourism are not known or taken into consideration. In order to get the local residents involved in tourism policies, it is necessary for them to have a favorable attitude towards tourism. Thus, in this paper we present the results of a research project, in which the attitudes of residents of a rural community in the Central Asia area were examined. The employed methodology included in-depth interviews, as well as a Likert-type questions questionnaire which included cognitive, affective and behavioral components. The main findings suggest the existence of favorable attitudes; However, due to failures in planning and training, people show little enterprising or proactive behavior.